Colonial history and global economics distort our understanding of deep-time biodiversity - Raja Schoob, Nussaibah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2021)
Sampling biases in the fossil record distort estimates of past biodiversity. However, these biases not only reflect the geological and spatial aspects of the fossil record, but also the historical and current collation of fossil data. We demonstrate how the legacy of colonialism and socioeconomic factors, such as wealth, education and political stability, impact the global distribution of fossil data over the past 30 years. We find that a global power imbalance persists in palaeontology, with researchers in high- or upper-middle-income countries holding a monopoly over palaeontological knowledge production by contributing to 97% of fossil data. As a result, some countries or regions tend to be better sampled than others, ultimately leading to heterogeneous spatial sampling across the globe. This illustrates how efforts to mitigate sampling biases to obtain a truly representative view of past biodiversity are not disconnected from the aim of diversifying and decolonizing our discipline.